LEGAL PRINCIPLES OF COOPERATION OF STATES WITH INTERNATIONAL FINANCIAL ORGANIZATIONS - Shamraiev, Vasyl (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2025)
Introduction. The article is devoted to the analysis of international legal support for cooperation of states with international financial organizations (IFOs). It aims to reveal the current state and prospects for the development of international economic cooperation through the improvement of international legal norms that regulate macroeconomic support to states by international financial organizations. The article focuses on the analysis of the founding agreements of such financial organizations as the IMF, EBRD, IBRD, etc., bilateral agreements between IFIs and individual states, as well as soft law norms in this area, which are not binding, but significantly affect national legal regulation.Summary of the main research findings. The main part of the study highlights the main approaches to defining the concept of "international financial organizations" and analyzes the founding documents as the legal basis for their functioning. The author identifies the international legal basis for cooperation between states and IFIs, which is usually drawn up in the form of memoranda of understanding, loan agreements, letters of intent and cooperation programs. A separate block is also formed by soft law norms, since IFIs in the process of developing cooperation issue analytical reports, recommendations, financial policy standards, which are not binding, but significantly affect the national economic law of individual states. The article analyzes such international financial organizations as the IMF, whose main role is to ensure currency stability, lending, and monitoring macroeconomic policy; the World Bank, which is a group of institutions that lend to development and infrastructure projects; the European Bank for Reconstruction and Development, which is focused on the development of market economies, the reform of post-Soviet countries, and finances public and private projects in the economy, energy, and innovation. Within the framework of the development of cooperation with IFIs, member states have the legal capacity to conclude international agreements; are entitled to participate in management (through voting); and are responsible for complying with obligations, including in the budgetary and debt spheres.Conclusion. The conclusions emphasize the importance of understanding the latest challenges facing states in the development of economic cooperation and the importance of improving the international legal framework, especially in the field of regulating the functioning of IFIs. The main problems in this area include the imperfect legal provision of lending conditions, which are sometimes perceived as interference in the domestic policy of a particular state; problems of the balance of sovereignty and enforcement, etc. In view of this, further reform of the voting system within individual international financial organizations, improvement of transparency procedures and strengthening of the legal status of soft law norms in national legal systems are considered promising areas for improving the legal framework in the sphere of cooperation of individual states with IFIs.